PELAKSANAAN PEMBELAJARAN IPS PADA SMP TERBUKA 02 KECAMATAN BANJARMASIN UTARA TAHUN AJARAN 2014/2015 DALAM PENINGKATAN KUALITAS PEMBELAJARAN - Roseda Rahmayani (JURNAL SOCIUS, 2015)
For children who have difficulty continuing school because of economic necessity, through the open junior high they can acquire the necessary educational services. , SMP Terbuka aims to provide learning opportunities more widely to children graduate SD / MI or equal who can not attend secondary school education Regular due to many barriers it faces. The existence of open SMP is perceived necessary and help students who are in a weak economic conditions or dropping out of school in a letter of graduation or diploma, so that children can also compete to further levels of schooling. This study aims to describe and analyze the implementation of social studies learning, student activities and the management of the Junior Open 02 North Banjarmasin Academic Year 2014/2015. This research approach is qualitative survey approach, and retrieval of data using observation sheets, interview and documentation. Based on the results of the study found that the teachers teaching social studies in the , SMP Terbuka 02 North Banjarmasin Academic Year 2014/2015 is already quite good, although there are some items that have not reached the maximum, and to aktiviats students have also been good, while for the management of the teaching provided is sufficient adequate.Keywords: curriculum development, teacher IPS, SMP Terbuka